Peer effects, industry concentration and capital structure: evidence from emerging market economies - Isma Zaighum; Ameenullah Aman; Mohd Zaini B. Abd Karim (Journal of Applied Economics, 2024)
This study investigates the relationship between peer effects and corporate capital structure with the intervening effect of industry concentration. The methodology involves instrumental variable approach in the regression results from OLS and two-stage least squares (2SLS) with fixed effects. Empirical evidence shows that peers’ leverage decisions are significant determinant for a firm’s leverage decisions. Moreover, peers matter more when firms are operating in the competitive environments and same is not true for firms belonging to concentrated environment. These findings imply that the financial policymakers may device customized policies for competitive and concentrated markets to restrict the downside risk of debt financing.